Development of bioactive PLA nanofiber wound dressings with Hypericum perforatum and zeolite - Caliskan, Seviye Nur; Farrah, Yara; Demircan, Nazlican; Yilmaz, Berke Veli; Alaca, Yigit Furkan; Pilavci, Esra; Kanli, Zehra (Elsevier, 2026)
This study presents the development of innovative wound dressings using Poly (Lactic Acid) (PLA) nanofibers functionalised with Hypericum perforatum (HP) extract and natural zeolite (ZEO). Nanofibers were fabricated via electrospinning and characterised. Results revealed that HP and ZEO significantly enhanced the thermal stability, mechanical strength, and biocompatibility of the nanofibers. When in vitro release of HP was analyzed, it was found to be finally released within 18 days. HP and ZEO together were increased the mechanical strength to the value of 1.84 +/- 0.53 MPa. This study highlights the synergy of natural bioactive compounds and sustainable materials in creating advanced wound care solutions.
Keywords: Electrospinning; Hypericum perforatum; Wound healing